Exploratory metabolomic analysis for characterizing the metabolic profile of the urinary bladder under estrogen deprivation - Zhang, Wei; Yang, Qingbo; Song, Yingying; Liu, Wenheng; Li, Yao (Frontiers in Endocrinology, 2024)
Background: Estrogen homeostasis is crucial for bladder function, and estrogen deprivation resulting from menopause, ovariectomy or ovarian dysfunction may lead to various bladder dysfunctions. However, the specific mechanisms are not fully understood.We simulated estrogen deprivation using a rat ovariectomy model and supplemented estrogen through subcutaneous injections. The metabolic characteristics of bladder tissue were analyzed using non-targeted metabolomics, followed by bioinformatics analysis to preliminarily reveal the association between estrogen deprivation and bladder function.We successfully established a rat model with estrogen deprivation and, through multivariate analysis and validation, identified several promising biomarkers represented by 3, 5tetradecadiencarnitine, lysoPC (15:0), and cortisol. Furthermore, we explored estrogen deprivationrelated metabolic changes in the bladder primarily characterized by amino acid metabolism imbalance.This study, for the first time, depicts the metabolic landscape of bladder resulting from estrogen deprivation, providing an important experimental basis for future research on bladder dysfunctions caused by menopause.